A Layered Architectural Model For Music Education: Malaysian Music On The World Wide Web - Minni, Ang kim Huai (1998)

(untitled)
To date, no research has yet been published on the subject of web architectures for music. The two-layered web architecture for Malaysian music, designed and developed in this study, can be applied as a model of web architecture for music education, specifically for the introduction of the music of a particular country or region. The model is designed and developed in two phases: the building of the subject architecture, or the content development phase; and the design and development of the application architecture. However, no comprehensive classification method for Malaysian music currently exists. Furthermore, information about all the various types of music in Malaysia is not easily available. The research includes the collection of information about Malaysian music from existing data sources and through field research, undertaken to obtain information